Fostering Biodiversity: Unleashing the Potential of Refugia to Enhance Arthropod Diversity in Chili (Capsicum annuum L.) Farms - Reksiana, Catur Putri Enggit; Windriyanti, Wiwin; Kusuma, Ramadhani Mahendra (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: The utilization of Integrated Pest Management (IPM) offers a solution to chili cultivation pest challenges by implementing ecological engineering strategies, such as planting refugia. These refugia serve as SNAP (Shelter, Nectar, Alternative Food, and Pollen) sources for beneficial insects. This study aimed to assess the impact of refugia planting on arthropod-type diversity and explore the influence of abiotic factors on arthropod populations. Methods: Conducted from February to May 2023, the research utilized various traps (sweep net, yellow trap, pitfall trap, and light trap) and visual control for specimen collection. Results: The identification revealed the presence of three classes, ten orders, and 31 families. Arthropod populations in chilli fields with refugia totaled 867 individuals, whereas those without refugia amounted to 475. Conclusions: Planting refugia led to an elevated diversity index and evenness of arthropods, coupled with a lower dominance index compared to fields without refugia. Surprisingly, temperature and air humidity did not exhibit a significant impact on the arthropod population in chilli fields.